Strength development of phosphoaluminate cements in a CO2-containing environments at 110 °C: synergistic evolution of compressive strength, hydration products and micro-morphology, and carbonation mechanism - Yuan, Bin; Yang, Shuo; Zhang, Xingyang; Zheng, Zehao; Xu, Bihua (Geoenergy Science and Engineering, 2025)
Phosphoaluminate cements are able to meet the high temperature and high CO2 content environments faced by oil and gas well cementing, owing to their high temperature and corrosion resistance. However, up to now, there is no research to clarify its compressive strength, hydration product changes and corrosion mechanism in such complex environments. Therefore, this paper analyzes the compressive strength and type of hydration products of phosphoaluminate cement stones at 110 °C and CO2 environments with different curing times and after corrosion. It was shown that the permeability of phosphoaluminate cement stone first decreased and then increased with the increase of the curing time, while the compressive strength kept increasing, and the specimens' compressive strength after corrosion still maintains a very high level. The stable existence of hydroxyapatite (Ca5(PO4)3OH) and hydrated aluminate (C3AH6), as well as the persistent generation of main hydration products (hydrated phosphate (CPH) and hydrated phosphoaluminate (CAPH)), and their morphology always maintains a uniform distribution of flakes and fibers, together guarantee the stable growth of compressive strength. The corrosion mechanism shows that Al(OH)3 and CaCO3, generated by the corrosion of CPH, CAPH with C3AH6 and CAP with CA, had a positive affect on pore development. At the same time, Ca10(PO4)6CO3 generated by the corrosion of some Ca5(PO4)3OH will maintain the original hexagonal structure to form a protective layer, and H3PO4 released by the corrosion of hydration products and reactive minerals will lead to an increasingly acidic solution. This prevents the diffusion of CO2 toward the internal cement stone, which in turn further inhibits corrosion. •Revealed mechanisms enhancing strength and resisting carbonation in PAC.•Uniform microstructure from CPH/CAPH drives evolution of compressive strength.•Carbonation forms Al(OH)3-CaCO3, boosting durability via denser pores.•Dual protection by Ca10(PO4)6CO3/H3PO4 impedes CO2 penetration and reaction kinetics.